Sistema de reabilitação baseado em técnicas de captura de movimento para tratamento da lombalgia mecânica - Damasceno, Eduardo Filgueiras (2013)
The Lumbago or commonly called "low back pain" is a frequent cause of morbidity and disability work, only surpassed by headache (headache) in the range of painful disorders affecting modern society, and the treatment is based on medication (painkillers) to relieve the symptoms of pain and recommending therapeutic exercise. However, when these exercises are performed and no longer perceived pain, the patient drops the treatment, and in many cases, having its range of movement fully reestablished. To mitigate this index abandoned therapies motivators several techniques have been employed, such as the use of digital games and entertainment interfaces. However, these approaches only emerge the playful part of treatment showing no concrete data on the occupational or even exercise performance and its efficiency in treatment. Therefore, this work describes a rehabilitation system based on motion capture techniques for the treatment of a type of low back pain, mechanical low back pain. This thesis presents techniques use motion capture environments applied to motor rehabilitation with some devices such as electrogoniometer, extensometer, accelerometer and other common interaction devices such as webcams, video game console (Nintendo WiiTM) and motion sensor MS-KinectTM. The motivation of the work is based on the fact that motion capture systems for video devices tend to be more economically viable, however the systems capture current video showed the following limitations: the overlap and occlusion of the markers, the disparity optical cameras the field of view and their geometric constraints. Therefore, this work presents an alternative proposal capture by multiple cameras in conjunction with the analysis of the intrinsic parameters of the cameras involved in the process to mitigate these limitations. For the analysis of motion captured was prototyped a system that meets the specifications on the biotype of the patient and an adapted questionnaire about their inability to move that, from these, form a set of information that supports the decision about treatment with exercise suggestions . In order to validate the information in the system as well as your business rules, an evaluation has made with a group of five therapists, and presented an analysis of the interface has performed by 20 patients. Those patients were surveyed volunteers. Through this analysis was possible to identify the potential of the prototype, as well as highlight the strategies for implementing even small physiotherapy clinics. Especially those that have no spaces or volume of investment in infrastructure for systems acquisition motion capture large - very important for analysis and recommendation of new exercises during a rehabilitative therapy.